Versatile process for the stereodiverse construction of 1, 3-polyols: iterative chain elongation with chiral building blocks. Issue 9 (17th December 2015) - Bredenkamp, Angela; Wegener, Michael; Hummel, Sara; Häring, Andreas P.; Kirsch, Stefan F.
Abstract : The iterative synthesis of all stereoisomers of 1, 3-polyols by use of chiral building blocks is presented. Abstract : A versatile process for the construction of 1, 3-polyols, a key structural element of polyketide-type natural products, is presented. The modular synthesis strategy involves the iterative chain elongation with novel four-carbon building blocks to access all possible stereoisomers of a growing 1, 3-polyol chain. These chiral building blocks are designed to install four carbon atoms with two stereogenic centres by performing only four experimentally simple steps per elongation cycle, thus making these building blocks attractive for the realization of a universal platform from which to access a diverse range of polyketidic molecules.